Sparse allele vectors and the savvy software suite - LeFaive, Jonathon; Smith, Albert V; Kang, Hyun Min; Abecasis, Gonçalo (Bioinformatics (Oxford, England), 2021)
Abstract Summary The sparse allele vectors file format is an efficient storage format for large-scale DNA variation data and is designed for high throughput association analysis by leveraging techniques for fast deserialization of data into computer memory. A command line interface has been developed to complement the storage format and supports basic features like importing, exporting and subsetting. Additionally, a C++ programming API is available allowing for easy integration into analysis software. Availability and implementation https://github.com/statgen/savvy. Supplementary information Supplementary data are available at Bioinformatics online.